Letter to the Editor Concerning “Why is Palliative Care Training During the Portuguese Family Medicine Residency Program Not Mandatory?” - Pimentel, Bernardo; Barosa, Mariana; Caiado Ferreira, Pedro; Neto Gonçalves, Tiago; Ramalho Rocha, Filipa; Galriça Neto, Isabel (Acta Médica Portuguesa, 2022)
N/a.